2015
DOI: 10.2134/agronmonogr47.c15
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia: Measurement Issues

Abstract: Historically, there has been a lack of reliable, fast-responding, and sensitive sensors for the measurement of NH 3 . There are several sensors becoming available and this review will not try to characterize available sensors because technologies are rapidly changing. There are, however, several classes of sensors for NH 3 measurement. Gas-WashingThis technique has been used as a standard for many years. Much of the early work on atmospheric transport was accomplished, by necessity, using this 348 HARPER Fig. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 109 publications
(134 reference statements)
0
22
0
1
Order By: Relevance
“…Ammonia mixing ratios are expected to be positively correlated with air temperature due to its combined effect on raising the NH 3 vapor pressure, reducing its water solubility, and enhancing the emission potential and source strength (Eilerman et al, ; Grant et al, ; Harper, ; Zhang et al, ). Further, the gas‐particle phase partitioning of NH 4 NO 3 is temperature dependent, where warmer air temperatures favor the gas phase (Seinfeld & Pandis, ).…”
Section: Resultsmentioning
confidence: 99%
“…Ammonia mixing ratios are expected to be positively correlated with air temperature due to its combined effect on raising the NH 3 vapor pressure, reducing its water solubility, and enhancing the emission potential and source strength (Eilerman et al, ; Grant et al, ; Harper, ; Zhang et al, ). Further, the gas‐particle phase partitioning of NH 4 NO 3 is temperature dependent, where warmer air temperatures favor the gas phase (Seinfeld & Pandis, ).…”
Section: Resultsmentioning
confidence: 99%
“…Acid traps were used to measure the NH 3 volatilization occurring within the wind tunnels and were composed of a cylinder (41 mm O.D., 200 mm height), fitted dispersion tube (250 mm), rubber stopper (#8), and an overflow tube (test tube fitted with a #4 stopper). The acid trap technique can be used to measure the concentration of NH 3 from enclosure methods, such as the wind tunnel method, as fast sampling and high sensitivity analysis are not required (Harper 2005). However, great care is needed, such as proper cleaning of glassware between sample timings, with this technique as it is prone to sample contamination.…”
Section: Ammonia Measurements Wind Tunnel Methodsmentioning
confidence: 99%
“…Including data covering a wider range of measurement techniques, such as static or dynamic chambers or wind tunnels, could widen the geographical coverage -for example, a number of studies based on enclosure or tracer techniques would be available for China (L. Zhang et al, 2018). However, the effects of heterogeneity in the measurement techniques would need to be assessed carefully, since systematic differences (Bouwman et al, 2002;Sintermann et al, 2012;Harper, 2005) have been found between the volatilization losses measured using different techniques.…”
Section: Model Evaluationmentioning
confidence: 99%
“…Volatilization of ammonia (NH 3 ) from livestock wastes and synthetic fertilizers forms a globally significant pathway of nutrient losses in agricultural ecosystems (Bouwman et al, 1997;Beusen et al, 2008;Battye et al, 2017). Once emitted to atmosphere, ammonia contributes to the formation of secondary aerosols with implications for public health and climate (Heald et al, 2012;Paulot et al, 2016). Deposition of ammonia and other reactive nitrogen species onto natural ecosystems has widely documented adverse effects on biodiversity (Duprè et al, 2010;Payne et al, 2017), but also potentially significant effects on ecosystem productivity (Zaehle and Dalmonech, 2011).…”
Section: Introductionmentioning
confidence: 99%